Precios relativos y exportaciones manufactureras españolas: ¿explotan las empresas industriales una cadena de valor multinacional? - Aláez, Ricardo; Fernández, Ana; García, Begoña (Estudios de Economía, 2016)
This paper analyses the Spanish manufacturing exports to the European Union.A panel data approach is used to test the hypothesis that there are differencesamong manufacturing branches exports in relation to their elasticity to shortterm variations in the real effective exchange rate index of the peseta. The mainresult is that exports of manufacturing branches controlled by local firms aremore sensible to relative prices changes, but these branches have reduced theirshare on overall exports in the under consideration period. Furthermore, thosemanufacturing branches controlled by foreign-owned firms have revealedthemselves less sensible to conjunctural variations in the real effective exchangerate index of the peseta, but have augmented their share in overall export value.